The Criminal Law Counteraction to Obstruction of Mobilization in Ukraine: Current Challenges and Solutions in the Context of the Russian-Ukrainian War - Pysmenskyy, Yevhen (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The intensification of the mobilisation process taking place in Ukraine, given the new phase of the Russian-Ukrainian war, which began on 24 February 2022 with Russian troops’ full-scale invasion of the territory of Ukraine, requires criminal law regulation. One of the negative influences on this process is the behaviour of those who obstruct mobilisation. Based on the study of the current law enforcement practice, such behaviour is charged under Article 114–1 of the Criminal Code of Ukraine and is considered one of the ways of obstructing the lawful activities of military formations. This article attempts to determine the specificities of such a criminal law response to cases of obstruction of mobilisation by analysing the practice of applying Article 114–1 of the Criminal Code of Ukraine, as this provision is used to counteract the obstruction of mobilisation. Research has revealed some positives and flaws concerning the description of the formulation and content of the charge; the determination of the motives for the criminal offence; the characterization of the person accused; the results of the case based on the charge; and the correctness of qualifying the actions of persons who obstruct mobilisation or otherwise facilitate evasion of military duty under Article 114–1 of the Criminal Code of Ukraine. It is concluded that the current approach to developing effective practices for counteracting obstruction of mobilisation requires change. Eliminating the identified flaws and amending criminal legislation is necessary for its more effective application.